USP7 Inhibition Alleviates H2O2-Induced Injury in Chondrocytes via Inhibiting NOX4/NLRP3 Pathway - Liu, Gang; Liu, Qingbai; Yan, Bin; Zhu, Ziqiang; Xu, Yaozeng (Frontiers in Pharmacology, 2021)
Osteoarthritis (OA), the most common form of arthritis, is a very common joint disease that often affects middle-aged to elderly people. However, current treatment options for OA are predominantly palliative. Thus, understanding its pathological process and exploring its potential therapeutic approaches are of great importance. Rat chondrocytes were isolated and exposed to hydrogen peroxide (H2O2) to mimic OA. The effects of H2O2 on ubiquitin-specific protease 7 (USP7) expression, reactive oxygen species (ROS) levels, proliferation, inflammatory cytokine release, and pyroptosis were measured. USP7 was knocked down (KD) or overexpressed to investigate the role of USP7 in OA. Co-immunoprecipitation (Co-IP) was used to study the interaction between USP7 and NAD(P)H oxidases (NOX)4 as well as NOX4 ubiquitination. NOX4 inhibitor was applied to study the involvement of NOX4 in USP7-mediated OA development. USP7 inhibitor was given to OA animals to further investigate the role of USP7 in OA in vivo. Moreover, H2O2 treatment significantly increased USP7 expression, enhanced ROS levels, and inhibited proliferation in rat chondrocytes. The overexpression of USP7 enhanced pyroptosis, ROS production, interleukin (IL)-1β and IL-18 levels, and the expression level of NLRP3, GSDMD-N, active caspase-1, pro-caspase-1, matrix metalloproteinases (MMP) 1, and MMP13, which was abolished by ROS inhibition. The USP7 KD protected rat chondrocytes against H2O2-induced injury. Co-IP results showed that USP7 interacted with NOX4, and USP7 KD enhanced NOX4 ubiquitinylation. The inhibition of NOX4 blocked the pro-OA effect of USP7. Moreover, the USP7 inhibitor given to OA animals suppressed OA in vivo. USP7 inhibited NOX4 ubiquitination for degradation which leads to elevated ROS production. ROS subsequently activates NLPR3 inflammasome, leading to enhanced production of IL-1β and IL-18, GSDMD-N-dependent pyroptosis, and extracellular matrix remodeling. Thus, UPS7 contributes to the progression of OA via NOX4/ROS/NLPR3 axis.